THE STUNTING PREVENTION EFFORTS THROUGH COUNSELING ACTIVITIES AND SUPPLEMENTARY FEEDING IN BATU HULA VILLAGE, BATANGTORU DISTRICT SOUTH TAPANULI DISTRICT: STUNTING PREVENTION EFFORTS THROUGH COUNSELING ACTIVITIES AND SUPPLEMENTARY FEEDING IN BATU HULA VILLAGE, BATANGTORU DISTRICT SOUTH TAPANULI DISTRICT - Dongoran, Rini Fitriani; Nasution, Nurlaila; Sari, Apriana; Siregar, Isra Hotningsih; Amanda, Desi Latifa; Lestari, Maya; nuraini, Intan; Rangkuti, Salsabila; Siregar, Puja; Ramadani, Dandi; Komala, Sri Indah; Astuti, Yulia (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Batu Hula villages is one of the villages in kecamatan Batang Toru ,Kabupaten tapanuli selatan. Batu Hula Village is recorded to have a fairly high stunting rate, it is known that the latest data until August 2022 there are 2 children in Batu Hula Village who are indicated to be stunted. Stunting is caused by a lack of nutritional intake for a long time in the first 1000 days of life (HPK), which is a critical period, the lack of parental knowledge will greatly affect children's nutritional intake. So in this case, it is necessary to prevent stunting problems by providing understanding to the community in deciding the high stunting rate in Batu Hula Village. In this case, Batu Hula Village Stunting-Thematic KKN students carried out Stunting Counseling activities which were also coupled with the distribution of PMT (Supplementary Food Provision) for pregnant women and Toddler children aimed at increasing the knowledge of parents how important it is to maintain children's nutritional intake even during pregnancy to prevent stunting.